Treatment of Proximal Hamstring Tendinopathy with Individualized Physiotherapy: A Clinical Commentary - Aidan Rich; Jillianne Cook; Andrew Hahne; Jon Ford (International Journal of Sports Physical Therapy)
Proximal hamstring tendinopathy (PHT) can occur in active and sedentary people and presents clinically as localised lower buttock pain with activities including prolonged sitting, squatting, and walking uphill or running. A recent systematic review of interventions for PHT reported insufficient evidence to recommend one intervention over another. The most commonly recommended treatment for PHT by experts is education and exercise. Exercise for PHT aims to restore kinetic chain function and loading capacity of the hamstring complex. The purpose of this commentary is to outline an education and exercise program developed for treating PHT utilizing principles successful in clinical trials for other tendinopathies adapted to the specific anatomical and biomechanical considerations of the proximal hamstring complex.